ANALISIS STRATEGI PEMASARAN DAN MODAL KERJA TERHADAP KEBERHASILAN USAHA PADA USAHA KULINER DI KECAMATAN BATURAJA TIMUR - Universitas Baturaja, Dahlia (Jurnal Manajemen, 2021)
The aim of this research is to analize the marketing strategies and working capital on the success of the culinary business in the East Baturaja district. The data used are primary data with data collection methods in the form of a questionnaire totaling 16 for variable X and 10 statements for variable Y which are scored based on a Likert scale and distributed to 65 respondents. The analysis was carried out quantitatively using multiple linear regression to show whether there was an influence between marketing strategy (X1) and working capital (X2) on business success (Y), hypothesis testing was carried out by partial and simultaneous testing. Based on the results of the analysis, it can be concluded: first, there is a positive and significant influence between marketing strategy (X1) and working capital (X2) on business success (Y) in culinary business in East Baturaja sub-district, second, that the analysis results of the coefficient of determination (R square) shows that there is a positive and significant influence between marketing strategy (X1) and working capital (X2) on business success (Y) of 0.553 or 55.3%, while the remaining 44.7% is influenced by other factors not included in this research.